(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The place of innovative activity in the process of life cycle of the enterprise is explored in the article. Features of construction of the managerial accounting in the agricultural enterprises with use of innovations are given. The place of innovative activity in the process of conducting economic activity by agricultural entity. Determined, that between managerial accounting and innovative agrotechnologies there is an interaction built on the basis of bilateral interrelation and direct influence on each other. Developed a block diagram of the construction and operation of managerial accounting in the interaction and interdependence with all components of the enterprise in a single holistic mechanism, which allows to determine the features of the introduction of innovative agricultural technologies. Graphically shows the schematic ratio of income and expenses for the introduction of innovative agricultural technologies. The classification is offered of incomes and expenses on a number of signs concerning introduction of innovative agrotechnologies, proceeding from features of the average statistical agricultural entity.